Developing supplementary reading materials to promote critical thinking for the X grade students of vocational high school based on the 2013 Curriculum - Cahyani Wuri Utami (Universitas Sarjanawiyata Tamansiswa, 2020)
This research is aimed at developing supplementary reading materials to promote critical thinking as a part of the 21st-centuryÂ competencies (Critical thinking, Creativity and Innovation, Communication and Collaboration) and to reveal the effectiveness of the developed product. The methodology was Research and Development by Borg and Gall (1983). The research steps consist of three main stages; (1) preliminary study covering document analysis, classroom observation, and need analysis, (2) development covering drafting, internal experts judgement, revision, a prototype of the product, (3) field testing covering try out, reflection and interview, external expert judgement, revision, and final product. In analyzing the data, the researcher used descriptive qualitative research. It was adapted from Qualitative Data Analysis by Miles, Huberman & Saldana (1994) that are condensing data, displaying data, drawing, and verifying conclusion. The results of the preliminary study showed that supplementary reading materials to promote the 4â€™Cs were needed. The textbook evaluation revealed that there were four chapters (chapter 1, chapter 5, chapter 8 and chapter 12) which need to be developed. In need analysis, the researcher interviewed three English teachers and nine students who were in low, middle and high level from the same class. Based on the data, the teachers and the students required the developed product. The researcher then made abound of drafts which were then revised into the prototype of the product. The developed product was tried out in class X TKJ A SMKN 1 Saptosari by having collaboration with the fellow teachers. To catch the real situation, the researcher recorded the teaching and learning process, wrote the transcripts, noted the classroom observation, and did reflection. After the final revision, the supplementary reading materials came to the final product. The try out proved that the developed supplementary reading materials are effective in promoting critical thinking. Based on the analysis, the students are able to complete the tasks that were designed to promote critical thinking ( making predictions, differentiating relevant and irrelevant information, relating different concepts, thinking inductively, and comparing or analyzing the texts).